FACULTY MEMBERS’ TECHNOLOGICAL PROFICIENCY, SUPPORT AND OBSTACLES - Gabriel Jessie T. Guevarra; Thelma D. Manansala; Lemuel Fontillas; Ramon Bantugan; Jayson Nicholas R. Viray (LPPM UNiversitas Bina Mandiri Gorontalo, 2024)
The advent of flexible online learning because of the pandemic has challenged Higher Education Institutions to think of innovative, creative, and effective ways to deliver lessons online. Video-based learning modules have become necessary for faculty members to deliver their online classes. With this, the researchers assessed the technological proficiency, support, and obstacles of the Department of Arts and Sciences (DOAS) faculty in producing these instructional videos. Through a survey administered among the participants from different subject clusters of the department, findings showed that most respondents are proficient in operating a camera and can execute various camera shots, angles, and movements. However, they are not well-versed in the concept of camera exposure which could improve footage quality. Respondents are also proficient in editing their instructional videos by adding music, voice-over, texts, and sound effects. There is little training experienced in making instructional videos as respondents claimed, although they have access to technology which allows them to create such videos. Respondents are divided in receiving further training; some expressed a positive attitude towards it while the others saw obstacles such as the availability of gadgets and software, time amidst their full-time work, and being new to concepts on videography. Researchers recommended a video-based learning module that allows for flexible learning among the faculty members to further improve instructional videos given the constraints expressed.